Original paperSerum soluble tumour necrosis factor a receptor type I measurement in patients - Lis-Święty, Anna; Brzezińska-Wcisło, Ligia (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2007)
The aim of this study was to assess the usefulness of soluble tumour necrosis factor a type I receptor (sTNFaRI) concentration as a prognostic parameter of systemic sclerosis (SSc) development and progression. Serum sTNFaRI levels were measured by ELISA in 50 patients with Raynaud’s phenomenon (30 patients with Raynaud’s phenomenon alone, 20 SSc patients) and 15 healthy controls. Mean level of sTNFaRI in patients with Raynaud’s phenomenon without clinical symptoms of connective tissue disease was significantly increased compared with normal controls (p<0.05), but significantly lower compared with ISSc and dSSc (respectively p<0.01 and p<0.001). Mean level of sTNFaRI in both subgroups of patients with Raynaud’s phenomenon alone (patients with either abnormal nailfold capillary findings and/or positive antinuclear antibody and patients without this abnormality) did not differ statistically significantly. Mean level of sTNFaRI in dSSc was significantly higher compared with ISSc (p<0.0002). Mean level of sTNFaRI was also significantly higher in SSc patients with rapidly progressive systemic involvement than in patients in whom progression was mild (p<0.02). Serum levels of sTNFaRI in SSc correlated positively with skin score (p<0.05) and negatively with Raynaud’s phenomenon duration. These data convince for a role of TNF-a in pathogenesis of Raynaud’s phenomenon and SSc. Monitoring of sTNFaRI levels may be useful in assessment of SSc activity and severity and may be helpful to evaluate the risk of progression to SSc in patients with Raynaud’s phenomenon.